2020
DOI: 10.20944/preprints202001.0115.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrical Heating for Heavy Oil: Past, Current, and Future Prospect

Abstract: This paper presents a review of the electrical heating method for heavy oil recovery based on past, current, and future prospects of electrical heating. Heavy oil is one of the potential crude oil used as a link to reduce the crisis of light oil used today. The obstacle of heavy oil is a high viscosity and density in which thermal injection is a method for heavy oil recovery, but it results in economic and environmental issues. Electrical heating is one of the thermal methods by transferring heat into the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Drainage" (SAGD), hot steam is injected into an upper horizontal well, the oil flows down by gravity and is produced from another lower parallel horizontal well [110]. 2) "Steam Flooding" (SF) involves continuous steam injection into a vertical well to create a hot zone and drives the heated oil to another vertical well for production [108].…”
Section: Recovery Of Man-made Steam From Heavy Oil Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Drainage" (SAGD), hot steam is injected into an upper horizontal well, the oil flows down by gravity and is produced from another lower parallel horizontal well [110]. 2) "Steam Flooding" (SF) involves continuous steam injection into a vertical well to create a hot zone and drives the heated oil to another vertical well for production [108].…”
Section: Recovery Of Man-made Steam From Heavy Oil Reservoirmentioning
confidence: 99%
“…3) The Cyclic Steam Stimulation (CSS) also deploys vertical wells to pump cyclically high temperature/high pressure steam into the reservoir, stopping and injecting again to reduce the oil viscosity for recovery [110]. The steam for injections comes from heating the water by burning natural gas.…”
Section: Recovery Of Man-made Steam From Heavy Oil Reservoirmentioning
confidence: 99%
“…It was observed that heavy oil exploitation requires hot steam injection as a method for oil recovery. However, the impact often causes environmental problems, which means it has to be replaced by electrical heating to transfer the heat into the reservoir using an electric current (Hasibuan et al, 2020). This is the reason Felix & Din (2022) recommended transformer usage, which is capable of increasing and decreasing the voltage to stabilize high-voltage electrical systems.…”
Section: Verification Of Heavy Oil Distributionmentioning
confidence: 99%